2014
DOI: 10.1098/rsbl.2014.0418
|View full text |Cite
|
Sign up to set email alerts
|

Indirect evidence for elastic energy playing a role in limb recovery during toad hopping

Abstract: Elastic energy is critical for amplifying muscle power during the propulsive phase of anuran jumping. In this study, we use toads (Bufo marinus) to address whether elastic recoil is also involved after take-off to help flex the limbs before landing. The potential for such spring-like behaviour stems from the unusually flexed configuration of a toad's hindlimbs in a relaxed state. Manual extension of the knee beyond approximately 908 leads to the rapid development of passive tension in the limb as underlying el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…This observation is consistent with recent findings, which suggest that the rapid flexion of the hindlimb may be associated with elastic recoil of the limb after the hindlimbs are fully extended during takeoff (Schnyer et al, 2014). This interpretation is based on the fact that the intensity of muscle activation in hindlimb flexors decreases with hop distance despite an increase in the magnitude and rate of hindlimb flexion (Schnyer et al, 2014). In fact, we have also observed that the only hops where hindlimbs are somewhat extended at impact are extremely short hops.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This observation is consistent with recent findings, which suggest that the rapid flexion of the hindlimb may be associated with elastic recoil of the limb after the hindlimbs are fully extended during takeoff (Schnyer et al, 2014). This interpretation is based on the fact that the intensity of muscle activation in hindlimb flexors decreases with hop distance despite an increase in the magnitude and rate of hindlimb flexion (Schnyer et al, 2014). In fact, we have also observed that the only hops where hindlimbs are somewhat extended at impact are extremely short hops.…”
Section: Discussionsupporting
confidence: 82%
“…However, a more likely explanation may be that hindlimb flexion is primarily due to the elastic recoil of the limb during the aerial phase (Schnyer et al, 2014). If the hindlimb passively recoils when extended during take-off, then the behavior is not going to be modulated by altered sensory information or changes in motor control strategies (Schnyer et al, 2014). Finally, as our analysis only included stable landings, we cannot rule out the possibility that the addition of extrinsic loads increased the likelihood of unstable landings or crashes, which were not recorded or included in our analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In hopping toads, measurements of limb kinematics and electromyographic activity suggest that passive muscle elasticity helps to reposition the hindlimb to a flexed position during aerial phase of a jump, in preparation for landing (Schnyer et al, 2014). A systematic study of joint torques in passive rat hindlimbs showed that passive muscle forces establish a joint neutral position, from which the joint deviates as individual muscle units are removed by dissection (Wu et al, 2012).…”
Section: Evidence For Energy Storage and Recovery In Muscle Springsmentioning
confidence: 99%
“…Elbow kinematics were analysed bilaterally as in Cox & Gillis [6]. EMG data were analysed as described in Schnyer et al [9]. Differences between left and right forelimbs in touchdown times, TD L-R , m. anconeus onset timing, AO L-R , and intensity, AI L-R , were calculated by subtracting the value for the right limb from that of the left.…”
Section: (C) Data Analysismentioning
confidence: 99%